2018
DOI: 10.1016/j.nuclphysb.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Quantum periods for N=2 SU(2) SQCD around the superconformal point

Abstract: We study the Argyres-Douglas theories realized at the superconformal point in the Coulomb moduli space of N = 2 supersymmetric SU (2) QCD with N f = 1, 2, 3 hypermultiplets in the Nekrasov-Shatashvili limit of the Omega-background. The Seiberg-Witten curve of the theory is quantized in this limit and the periods receive the quantum corrections. By applying the WKB method for the quantum Seiberg-Witten curve, we calculate the quantum corrections to the Seiberg-Witten periods around the superconformal point up t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…With the conjectured relation (4.7), we find that the partition functions Z ǫ 1 ,ǫ 2 (A 1 ,A 3 ) and Z ǫ 1 ,ǫ 2 (A 1 ,D 4 ) are invariant under (ǫ 1 , ǫ 2 ) → (−ǫ 1 , −ǫ 2 ) with masses and the vev of Coulomb branch operators fixed. This invariance is consistent with quantum periods of Argyres-Douglas theories recently evaluated in [22,23,73]. The quantum periods are a I ≡ A I λ and a D I ≡ B I λ deformed by the Ω-background (ǫ 1 , ǫ 2 ) = ( , 0), where A I and B I are canonical 1-cycles of the Seiberg-Witten curve, and λ is the Ω-deformed Seiberg-Witten 1-form.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…With the conjectured relation (4.7), we find that the partition functions Z ǫ 1 ,ǫ 2 (A 1 ,A 3 ) and Z ǫ 1 ,ǫ 2 (A 1 ,D 4 ) are invariant under (ǫ 1 , ǫ 2 ) → (−ǫ 1 , −ǫ 2 ) with masses and the vev of Coulomb branch operators fixed. This invariance is consistent with quantum periods of Argyres-Douglas theories recently evaluated in [22,23,73]. The quantum periods are a I ≡ A I λ and a D I ≡ B I λ deformed by the Ω-background (ǫ 1 , ǫ 2 ) = ( , 0), where A I and B I are canonical 1-cycles of the Seiberg-Witten curve, and λ is the Ω-deformed Seiberg-Witten 1-form.…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…a D = ∂F /∂a. As shown in [22,23], the -expansion of these quantum periods for (A 1 , A r ) and (A 1 , D r ) theories have only even powers of . 34 This means that, at least in the limit of ǫ 2 → 0, the quantity ǫ 1 ǫ 2 log Z ǫ 1 ,ǫ 2 is invariant under (ǫ 1 , ǫ 2 ) → (−ǫ 1 , −ǫ 2 ).…”
Section: Conclusion and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…• It would be interesting to study the Nekrasov-Shatashvili limit [37] of the Ω-deformed (A 3 , A 3 ) theory. In this limit, combining the results of [38][39][40][41] with our formula, one can evaluate the deformed prepotential of the (A 3 , A 3 ) theory including both the perturbative and instanton parts.…”
Section: Jhep04(2021)205mentioning
confidence: 99%
“…(See also [27,28,29,30] for its relation to CFT. )In the previous papers [31,32], we have studied the quantum SW curves for the AD theories associated with N = 2 SU(2) SQCD, the (A 1 , A r )-type and (A 1 , D r )-type AD theories. We have calculated the quantum corrections to the SW periods up to the fourth order in the deformation parameter and confirmed that they are consistent with the scaling limit of the quantum periods of the UV theories.…”
mentioning
confidence: 99%